﻿Technical report of the preliminary findings of the informal survey, 1989-90: Hillside agriculture sub-project - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
52 páginas. Miscelaneous publications series A2/JM-91-007